Memory regulatory T cells in pregnancy - Chen, Zeyang; Zhang, Yanan; Kwak-Kim, Joanne; Wang, Wenjuan (Frontiers in Immunology, 2023)
Pregnancy requires the process of maternal immune tolerance to semi-allogeneic embryos. In contrast, an overreactive maternal immune system to embryo-specific antigens is likely to result in the rejection of embryos while damaging the invading placenta, such that the likelihood of adverse pregnancy outcomes can be increased. Regulatory T cells (Tregs) are capable of suppressing excessive immune responses and regulating immune homeostasis. When stimulating Tregs, specific antigens will differentiate into memory Tregs with long-term survival and rapid and powerful immune regulatory ability. Immunomodulatory effects mediated by memory Tregs at the maternal-fetal interface take on critical significance in a successful pregnancy. The impaired function of memory Tregs shows a correlation with various pregnancy complications (e.g., preeclampsia, gestational diabetes mellitus, and recurrent pregnancy losses). However, the differentiation process and characteristics of memory Tregs, especially their role in pregnancy, remain unclear. In this study, a review is presented in terms of memory Tregs differentiation and activation, the characteristics of memory Tregs and their role in pregnancy, and the correlation between memory Tregs and pregnancy complications. Furthermore, several potential therapeutic methods are investigated to restore the function of memory Tregs in accordance with immunopathologies arising from memory Tregs abnormalities and provide novel targets for diagnosing and treating pregnancy-associated diseases.